2013
DOI: 10.1063/1.4798374
|View full text |Cite
|
Sign up to set email alerts
|

Compression of scheelite-type SrMoO4 under quasi-hydrostatic conditions: Redefining the high-pressure structural sequence

Abstract: The high-pressure behavior of tetragonal SrMoO 4 was analyzed by Raman and optical-absorption measurements. Pressures up to 46.1 GPa were generated using diamond-anvil cells and Ne or N 2 as quasi-hydrostatic pressure-transmitting media. A reversible phase transition is observed at 17.7 GPa. A second transition is found at 28.8 GPa and the onset of a third one at 44.2 GPa. The pressure dependence of Raman-active modes is reported for the different phases and the pressure evolution of the fundamental band-gap r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 46 publications
14
46
0
Order By: Relevance
“…Both facts suggest that deviatoric stresses could strongly influence the high-pressure structural and vibrational behavior of wolframites as they do on related scheelite-type oxides. 17,18 In Table I, Since the multiferroic behavior of MnWO 4 was discovered, many works have been devoted to study its physical properties. However, most of those properties have been studied in the low-temperature range where the magnetic behavior shows up.…”
Section: Methodsmentioning
confidence: 99%
“…Both facts suggest that deviatoric stresses could strongly influence the high-pressure structural and vibrational behavior of wolframites as they do on related scheelite-type oxides. 17,18 In Table I, Since the multiferroic behavior of MnWO 4 was discovered, many works have been devoted to study its physical properties. However, most of those properties have been studied in the low-temperature range where the magnetic behavior shows up.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the frequency of each of the phonons of the doublet by making a Lorentzian multi-peak fitting analysis. 36 In order to illustrate this fact, we include in Figure 3 two insets (on the left-hand side) showing the asymmetric phonons and the two Lorentzian functions used to fit them.…”
Section: Amentioning
confidence: 99%
“…1,4,7,8 During the last decade, intensive investigations have been carried out on the structural evolution of MTO 4 -type ternary oxides under high-pressure (HP). They showed that compression is an efficient tool to improve the understanding of the main physical properties of vanadates, 9 phosphates, 10 chromates, 11 tungstates, 12 molydbates, 13 arsenates, 14 and many other MTO 4 compounds. 15 However, to the best our knowledge, an investigation of BiSbO 4 under pressure is still lacking in literature.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the most studied members of this family of materials have been the orthotungstates and orthomolybdates, which have many technological applications [11][12][13][14][15][16]. In special high-pressure (HP) studies of MTO 4 ternary oxides have generated a large amount of attention, with HP being an efficient tool in improving the understanding of their physical properties [3][4][5][6][7][8][9][10][11][12]. Recently, other compounds such as perrhenates [17] and orthotantalates [18] have also become the focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary oxides of the form MTO 4 have been extensively studied for their interesting physical properties, in particular, those oxides crystallizing either in the scheelite or the wolframite structure [1][2][3][4][5][6][7][8][9][10]. During the last decade, the most studied members of this family of materials have been the orthotungstates and orthomolybdates, which have many technological applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%